A highly transparent self-cleaning superhydrophobic surface by organosilane-coated alumina particles deposited via electrospraying1. Issue 21 (7th June 2015) - Yoon, Hyun; Kim, Hayong; Latthe, Sanjay S.; Kim, Min-woo; Al-Deyab, Salem; Yoon, Sam S.
<x xml:space="preserve">Abstract</x> A highly transparent self-cleaning superhydrophobic surface was prepared by electrospraying an organosilane-coated alumina precursor.